A NARRATIVE APPROACH OF PROFESSIONAL IDENTITY IN NOVEL TEACHER - Pablo Cortés González; Analía E. Leite Méndez; José Ignacio Rivas Flores (Tendencias Pedagógicas, 2015)
This paper points out the first results obtained in the research project ‘The construction of the professional identity of primary education degree students’ developed in Málaga. It analyses from narrative strategies, how professional identity is shaping to the novice teachers from his years of training and firs contacts of teaching. At the same time it is a way to visualize and interpret how the idea of professional development of this collective is constructed and how systematically is exposed by legislative, social changes. In the end, to understand the construction of teacher identity is a way to think new possibilities of professional development.